Altruism, personal benefit, and anxieties: a phenomenological study of healthy volunteers' experiences in a placebo‐controlled trial of duloxetine. (5th July 2016) - Kwakye, Isaac N.; Garner, Matthew; Baldwin, David S.; Bamford, Susan; Pinkney, Verity; Bishop, Felicity L.
Abstract : Objective: The objective of this study was to develop an in‐depth understanding of healthy volunteers' experiences of mental health trials. Methods: A qualitative study was nested within a healthy volunteer placebo‐controlled trial of duloxetine, a psychotropic drug used for treating patients with major depression and generalized anxiety disorder. Eight participants were interviewed, and data were analyzed using interpretative phenomenological analysis. Results: Interviewees described volunteering for the trial because they were interested in research, wanted the monetary incentive, wanted to help researchers, and wanted to be part of something. On entering the trial, participants considered the possible risks and described feeling anxious, excited, and determined; they had some clear expectations and some loosely held hopes about what would happen. During the trial, participants were curious about whether they were taking duloxetine or placebo, self‐monitored their bodies' reactions, and guessed which treatment they received. On being un‐blinded to treatment allocation after completing the trial, some participants' guesses were confirmed, but others were surprised, and a few were disappointed. Conclusions: Small changes to advertising/consent materials to reflect volunteers' motivations could improve recruitment rates to similar trials; "active" placebos might be particularly useful for maintaining blinding in healthy volunteer trials; and sensitive procedures are needed for un‐blinding participants to treatment allocation. Copyright © 2016 John Wiley & Sons, Ltd.